All-inorganic colloidal silicon nanocrystals—surface modification by boron and phosphorus co-doping. (18th May 2016) - Fujii, Minoru; Sugimoto, Hiroshi; Imakita, Kenji
Abstract: Si nanocrystals (Si-NCs) with extremely heavily B- and P-doped shells are developed and their structural and optical properties are studied. Unlike conventional Si-NCs without doping, B and P co-doped Si-NCs are dispersible in alcohol and water perfectly without any surface functionalization processes. The colloidal solution of co-doped Si-NCs is very stable and no precipitates are observed for more than 5 years. The co-doped colloidal Si-NCs exhibit size-controllable photoluminescence (PL) in a very wide energy range covering 0.85 to 1.85 eV. In this paper, we summarize the structural and optical properties of co-doped Si-NCs and demonstrate that they are a new type of environmentally-friendly nano-light emitter working in aqueous environments in the visible and near infrared (NIR) ranges.